2002
DOI: 10.1021/ie011022c
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Optimizing Polypropylene−Clay Nanocomposite Structure

Abstract: The structure of nanocomposites produced by melt-mixing polypropylene and 5 wt % of organically modified layered silicates with varying amounts of different maleated polypropylene compatibilizer grades has been analyzed with X-ray diffraction, transmission electron microscopy (TEM), and melt rheology. The extent of delamination in different nanocomposites has been quantified from analysis of several TEM images for each specimen by a product of the single particle volume fraction and the intrinsic viscosity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 18 publications
4
62
0
Order By: Relevance
“…It can be observed that irrespective of the method of preparation with increasing PPMA concentration the peak position shifts towards lower angles indicating improvement in the extent of intercalation of the polymer into the organoclay gallery. These results are similar to earlier reports [13,[32][33][34][35]. When the nanocomposites were prepared by direct mixing route and KPPSA was used as compatibilizer, the WAXD patterns show higher d-spacing for the clay as compared to that observed with the nanocomposites prepared using PPMA.…”
Section: Structure Of the Nanocompositessupporting
confidence: 90%
“…It can be observed that irrespective of the method of preparation with increasing PPMA concentration the peak position shifts towards lower angles indicating improvement in the extent of intercalation of the polymer into the organoclay gallery. These results are similar to earlier reports [13,[32][33][34][35]. When the nanocomposites were prepared by direct mixing route and KPPSA was used as compatibilizer, the WAXD patterns show higher d-spacing for the clay as compared to that observed with the nanocomposites prepared using PPMA.…”
Section: Structure Of the Nanocompositessupporting
confidence: 90%
“…This involves the exchange of hydrophilic cations on the clay surface with short-chain organic cations, such as alkyl ammonium ions. 11,12 The surface modification of clay, often referred to as organoclay, has shown improved compatibility with the polymeric matrix. 8,11 In some polymer matrixes, especially highly hydrophobic polyolefin polymers, organoclay could still not provide enough nanoclay-polymer interactions to produce a high degree of clay dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…0.1 wt%), for achieving a good improvement in morphology. In the case of both PE and PP/OLS nanocomposites, if the grafting level was higher than this limit value, a shift or even a disappearance of the basal refl ection peak of the OLS on the XRD diffraction pattern could be observed [51,72,77,78,92] .…”
Section: Random Copolymersmentioning
confidence: 96%
“…In fact, the hydrophilicity of the compatibilizer was seen to increase with the grafting level of MAH, thus improving the level of interaction between the polymer and the clay. In the case of the most common PO -g -MAH compatibilizers, the level of grafting ranged typically between 0.1 and 2 wt% [50,85,92,93] . In the case of MAH -functionalized PO, there was seen to be a limit value for the grafting level (ca.…”
Section: Random Copolymersmentioning
confidence: 99%